Trial of C. B. Reynolds For Blasphemy, at Morristown, N. J., May 1887: Defence - Ingersoll, Robert Green, 1833-1899; Baker, I. N. (Isaac Newton), 1838-1923 (Salt Lake City, UT : Project Gutenberg, 2011)
"Trial of C. B. Reynolds For Blasphemy, at Morristown, N. J., May 1887: Defence" by Robert G. Ingersoll is a historical account written in the late 19th century. The text details the defense of C. B. Reynolds, a freethought missionary accused of blasphemy for expressing his views through public lectures and a satirical pamphlet. Ingersoll's defense challenges the legitimacy of the blasphemy statute itself, arguing for the essential rights of free speech and intellectual liberty. The opening of the work introduces the context of Reynolds' indictment and provides insight into the trial's significance. It highlights the circumstances that led to the charge, including the hostile reactions from local religious groups during Reynolds' speeches. Ingersoll passionately articulates arguments regarding the importance of expressing one$1 (Bs honest thoughts, the historical misuse of blasphemy laws, and the need for intellectual freedom, setting the stage for a broader discussion about the rights of individuals against oppressive structures. This portion serves both as a defense for Reynolds and a call to uphold the principles of liberty in public discourse. (This is an automatically generated summary.)s
Release date is 2011-11-22
Produced by David Widger
Keywords: Reynolds, C. B. (Charles B.), 1832-1896 -- Trials, litigation, etc; Trials (Blasphemy) -- New Jersey -- Morristown; Freedom of religion -- United States; Freedom of speech -- United States